Empowering collaborative forest restoration with locally relevant ecological research - Matonis, Megan Shanahan, author; Binkley, Daniel, advisor; Battaglia, Mike A., committee member; Reid, Robin S., committee member; Schultz, Courtney A., committee member (Colorado State University. Libraries, 2015)
Collaborative forest restoration can reduce conflicts over natural resource management and improve ecosystem function after decades of degradation. Scientific evidence helps collaborative groups avoid undesirable outcomes as they define goals, assess current conditions, design restoration treatments, and monitor change over time. Ecological research cannot settle value disputes inherent to collaborative dialogue, but discussions are enriched by locally relevant information on pressing natural resource issues. I worked closely with the Uncompahgre Partnership, a collaborative group of managers, stakeholders, and researchers in southwestern Colorado, to develop research questions, gather data, and interpret findings in the context of forest restoration. Specifically, my dissertation (1) explored ways to better align collaborative goals with ecological realities of dynamic and unpredictable ecosystems; (2) defined undesirable conditions for fire behavior based on modeling output, published literature, and collaborative discussions about values at risk; (3) assessed the degree to which restoration treatments are moving forests away from undesirable conditions (e.g., homogenous and dense forests with scarce open habitat for grasses, forbs, and shrubs); and (4) looked at the validity of rapid assessment approaches for estimating natural range of variability in frequent-fire forests. The current practice of defining desired future conditions pulls managers and stakeholders into command-and-control thinking and causes them to dream away resource tradeoffs and the unpredictability of forest change. Instead, moving ecosystems away from undesirable states and reducing unacceptable risk might allow for diverse and socially acceptable conditions across forested landscapes. The concept of undesirable conditions helped the Uncompahgre Partnership come to agreement over types of fire behavior and stand conditions they wanted to avoid through management. I determined that restoration treatments on the Uncompahgre Plateau are generally moving forests away from undesirably dense conditions that were uncommon prior to Euro-American settlement. My assessment was largely based on data collected during collaborative workdays with the Uncompahgre Partnership. Our rapid assessment approach for estimating historical forest structure took a quarter of the time required for scientifically rigorous stand reconstructions, and it provided reasonably accurate estimates of tree density and spatial patterns. Our data on historical stand structure revealed that fragmentation and loss of open grass-forb-shrub habitat between tree groups were the most dramatic and undesirable changes occurring in frequent-fire forests over the past century. Many restoration treatments are focused on restoring spatial patterns in tree groups, with little attention to spatial patterns in open grass-forb-shrub habitat. I determined that the juxtaposition of tree groups with grass-forb-shrub habitat >6 m from overstory trees is important for restoring understory cover, diversity, and composition. Focusing on undesirable conditions in stands, such as high tree density and scarcity of grass-forb-shrub habitat, can help collaborative groups find common ground and design treatments that restore structure, composition, and processes in forest ecosystems.
Keywords: historical range of variability; ponderosa pine; undesirable conditions; open grass-forb-shrub habitat; collaboration; restoration